2022
DOI: 10.3390/land11081338
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Ability of Agricultural Socialized Services to Promote the Protection of Cultivated Land among Farmers

Abstract: Protecting and improving the quality of cultivated land is important to agricultural modernization. Based on data from a survey of 706 rice-growing households in Hunan, Jiangxi and Jiangsu, this paper uses the Probit model, CMP method and Biprobit model to systematically analyze the impact of agricultural socialized services on farmers’ cultivated land quality protection behaviors. This study finds that agricultural socialized services have a significantly positive impact on the adoption of soil testing formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Zhang et al (2022) showed through empirical research that agricultural outsourcing services can significantly promote fertilizer reduction through circuitous investment, market competition, and reputational incentives [ 18 ]. Cheng et al (2022) analyzed the survey data of rice farmers and found that agricultural socialized services have a significant positive impact on farmers’ adoption of soil testing formulas, which can improve the probability and degree of cultivated land quality protection [ 19 ]. Cai et al (2019) showed that the application of socialized services of green production, such as deep tillage, soil testing, and formulated fertilization in the pre-production, production, and post-production stages of food production, is the key to saving agricultural resources, improving environmental pollution and ensuring food security [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2022) showed through empirical research that agricultural outsourcing services can significantly promote fertilizer reduction through circuitous investment, market competition, and reputational incentives [ 18 ]. Cheng et al (2022) analyzed the survey data of rice farmers and found that agricultural socialized services have a significant positive impact on farmers’ adoption of soil testing formulas, which can improve the probability and degree of cultivated land quality protection [ 19 ]. Cai et al (2019) showed that the application of socialized services of green production, such as deep tillage, soil testing, and formulated fertilization in the pre-production, production, and post-production stages of food production, is the key to saving agricultural resources, improving environmental pollution and ensuring food security [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The social niche is also between the low and medium levels, and its level is relatively close to the level of the economic niche. Since the application of photovoltaic in agriculture can solve the problem of power consumption in agriculture [ 50 ], especially in remote areas, and the power output from the agrivoltaic system can be applied to all aspects of human society, photovoltaic agriculture plays a more prominent role in alleviating the contradiction between supply and demand of clean energy than the other three aspects of the social niche. Accordingly, photovoltaic agriculture can ensure energy security to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…The application of organic fertilizer is a knowledge-intensive technology and requires a high level of knowledge of farmers. However, in the state of decentralized operation in China, a single farmer cannot master the professional knowledge of organic fertilizer application based on his own experience ( 45 ). Agricultural socialized services can provide farmers with high-quality and sufficient agricultural technical guidance through various forms such as technical training, printing and distributing technical materials, and holding professional conferences to improve the utilization level of organic fertilizer.…”
Section: Theoretical Basismentioning
confidence: 99%